ANALYSIS OF THE QUALITY PARAMETER AND THE FATTY ACID CONTENT FROM THE FOUR OF INDONESIAN CONSUMED NUTS - Indra Topik Maulana; Tiara Deviani; Alfiah Nurulfikri (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Consumption of nuts is known to have a variety of health benefits. Nutritional contents in the nuts are needed, especially in order to provide healthy food. Nuts are rich in protein, carbohydrates, fiber, fatty acids, and bioactive compounds. There are four types of beans that are commonly consumed by Indonesian people, namely soybeans [Glycine max (L.) Merr], green beans [Vigna radiata (L.) Wilezek], peas (Pisum sativum L.), and red beans (Phaseolus vulgaris L). The purposes of this study were to produce data on the content of secondary metabolites, the value of quality parameters, and data on fatty acid content in four types of nuts. A series of research phases have been conducted including phytochemical screening, analysis of quality parameters, and analysis of fatty acid content using gas chromatography-mass spectroscopic methods (GCMS). The results showed that the four types of beans contained alkaloids and essential oils, and some of them contained flavonoids, tannins, saponins, and polyphenols. Analysis of quality parameters showed that the content of polar compounds was higher than the semi-polar and non-polar compounds. The largest yield of fatty oil was produced from soybeans (3.83%) followed by peas (1.25%), green beans (0.57%), and kidney beans (0.44%). The oils from the all both contained palmitic acid, LA, and stearic acid. Only green bean and red bean oil contained omega-3, namely ALA, in the amounts respectively 20.37% and 40%. Meanwhile, soybean and peanut oil contained LA 36.71% and 35.53% respectively.